The role of property in the capital markets - Sieracki, Karen; Liow, Kim Hiang (Journal of property investment & finance ;, 2008)
This e-book examines the importance oft the impact of the capital markets on the real estate market in terms of its pricing, availability of money and financial engineering. It is necessary for us to understand the relationship of capital markets to real estate and how it is demonstrated around the world.